2011
DOI: 10.1007/s10151-011-0727-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Doppler-guided hemorrhoid artery ligation: analysis of 90 consecutive patients

Abstract: Doppler-guided hemorrhoid artery ligation seems to be a safe and effective treatment option for all grades of hemorrhoidal disease. Further prospective randomized comparative studies are needed in order to fully evaluate the true role of DG-HAL in the surgical armamentarium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…Spyridakis et al . reported recurrence of 0% in grade II, 5% in grade III and 50% in grade IV at 12 months, whilst Faucheron et al . reported recurrence rates of 9% for grade III and 23.8% for grade IV at 36 months.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Spyridakis et al . reported recurrence of 0% in grade II, 5% in grade III and 50% in grade IV at 12 months, whilst Faucheron et al . reported recurrence rates of 9% for grade III and 23.8% for grade IV at 36 months.…”
Section: Resultsmentioning
confidence: 96%
“…Recurrence rates were universally higher in patients who had been diagnosed with higher-grade haemorrhoids. Spyridakis et al [18] reported recurrence of 0% in grade II, 5% in grade III and 50% in grade IV at 12 months, whilst Faucheron et al [19] reported recurrence rates of 9% for grade III and 23.8% for grade IV at 36 months. Similar findings were reported by other studies which stratified recurrence rates by preoperative grading [12,20].…”
Section: Recurrencementioning
confidence: 99%
“…We chose to assess recurrence at 12 months because published data suggest that most HAL and RBL recurrences occur within 1 year. 26 Several studies have shown that using HAL for higher-grade haemorrhoids or significant prolapse adversely affects the recurrence rate; 19,37,41,66,67 they also conclude that HAL is perhaps most effective for grade II and early grade III disease. We therefore limited our trial to this most clinically relevant patient population.…”
Section: Main Findingsmentioning
confidence: 99%
“…There are no existing RCTs that compare HAL with RBL, although there is now one non-randomised comparison with small numbers of patients. 41 …”
Section: Rationalementioning
confidence: 99%
“…14 In comparison with other surgical treatments for haemorrhoids, the recurrence rate for THD appears to be comparable with both stapled haemorrhoidectomy and excisional haemorrhoidectomy. 15,17,18 The complication profile of THD appears to be superior to stapled haemorrhoidectomy which has been associated with the risk of severe sepsis, rectal injury and mortality 6,19,20 as well as faecal urgency. 10 A randomized multicentre trial by Infantino et al comparing THD to stapled haemorrhoidectomy did not show any significant difference in recurrence rates at 17 months follow-up.…”
Section: Discussionmentioning
confidence: 99%